Effect of nanocellulose on the structure and properties of arrowroot starch films - Muhammad Firdaus, Abdul Halim; Mohd Sapuan, Salit; Zainudin, Edi Syams; Atiqah, Mohd Afdzaluddin (Industrial Chemistry Research Institute, 2026)
Effect of 1 and 3 wt% nanocrystalline arrowroot cellulose (ARNC) on the structure and properties of arrowroot starch (AS)-based films was investigated. The addition of ARNC increased the film density and reduced its water absorption, indicating improved moisture barrier properties. Furthermore, tensile strength increased (from 2.5 MPa to 4.3 MPa) and elongation at break (from 13.4% to 45%). Simultaneously, Young’s modulus decreased (from 65.7 MPa to 32.5 MPa), suggesting increased flexibility. FESEM analysis revealed good dispersion of cellulose nanocrystals in the composite, with a tendency to agglomerate at higher ARNC content.